THE ANALYSIS OF SCIENCE TEXTBOOK FOR FIFTH GRADE OF ELEMENTARY SCHOOL IN SAMBONG SUBDISTRICT, DISTRICT OF BLORA BASED ON SCIENTIFIC LITERACY ASPECTS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This study aims to explain scientific literacy aspects on science textbook for fifth grade used for Elementary School. Scientific literacy aspects involve (1) the knowledge of science, (2) the investigative nature of science, (3), science as the way of thinking, and (4) interaction of science, technology and society. The approach of this study was qualitative. This study used purposive sampling and the observed samples were three science textbooks that most used at Elementary School in Sambong Sub-District, District of Blora. The data of this study were obtained by using technique of documentation study based on scientific literacy aspects. The data analysis was done using descriptive statistics with percentage calculation. The result of this study showed that scope of scientific literacy aspects on books that were analyzed, especially in Biology, were 67,4% contains of the knowledge of science , 16,8% contains of the investigative nature of science, 13,3% contains of science as the way of thinking, and 2,5% contains of interaction of science, technology and society. The result of analysis indicated that books used were not show the balance of scientific literacy aspects where science as the body of knowledge aspect is still much greater than three other aspects.